(untitled) (Journal of Patan Academy of Health Sciences, 2024)
Introduction: COVID-19 is a disease caused by novel coronavirus SARS-CoV-2 that led to a global epidemic resulting in significant morbidity across all ages. This study is intended to find out the clinical presentation of COVID-19 in children and to compare them among different age categories in children. Method: This is a retrospective study done over the period of one year in COVID facility of Patan hospital. Demographic and clinical profile of children who were tested positive by polymerase chain reaction (PCR) were recorded. The data was compiled in Microsoft Excel 2021 and exported to Statistical Package for Social Sciences (SPSS) Version 27. Result: During the study period 1639 children were admitted in Patan Hospital with 136(8.30%) of them in the COVID facility. Among these, 41(30.14%) tested positive for SARS-CoV-2 with the median age of 2 years and 26(63.41%) were male. The cases were evenly distributed among infants 13(31.71%), under five 14(34.14%) and 5-14 years old 14(34.14%). The asymptomatic children were 8(19.51%) while 17(41.46%) had mild symptoms. Infants and preschool children had less severe presentation as compared to older children. Fever 33(80.45%) and cough/difficulty in respiration 8(19.51%) were the most common symptoms while respiratory signs like crackles 15(36.59%) and subcostal recession 9(21.95%) were the most common. Conclusion: SARS-COV-2 infection in children present with mild symptoms. Fever, respiratory signs and symptoms were common. There were no differences in morbidity among different age categories.